Research on Plug-and-Play Twin-Field Quantum Key Distribution - Park, Chang Hoon; Ki Woo, Min; Park, Byung Kwon; Kim, Yong Su; Kim, Sangin; Han, Sang Wook (International Conference on ICT Convergence, 2020)
In this paper, we have proposed a plug-and-play twin-field quantum key distribution scheme that has passive mode-matching characteristics of quantum signals and can be operated stably. Also, we have experimentally demonstrated the implementation feasibility of our proposed scheme.
Keywords: Passive mode; Plug and play; Quantum key; Quantum signals; plug-and-play; quantum key distribution; twin-field